Postectomia com Fios de Poligalactina ou Categute e Sutura com pontos separados e contínuos - BRENO DINIZ NOGUEIRA (2017)
INTRODUCTION: Circumcision is one of the most performed surgery in the world; about 30% of men are circumcised. Despite this, there are insufficient publications related to surgical techniques in adults. At birth 96% of men present physiological phimosis, which is the commom indication for surgical circumcision. Phimosis is defined as the inability to retract the foreskin due to the narrowing and/or adhesions in the penis glans. Circumcision is indicated when the physiological phimosis does not have spontaneous resolution. OBJECTIVES: (i) to compare the results of circumcision through the use of different surgical threads and suture techniques, as to the incidence of complications and scar quality, time and cost of the surgical procedure; (ii) to check for correlation among medical conditions for surgical circumcision, educational level, skin color, tabacco use and use of medications with the results of the surgery. METHOD: Eighty sleeve circumcisions were performed by a single surgeon. The patients were divided into four groups, through randomization: poligalactine continuous and separated suture and catgut continuous and separated suture. Patients were evaluated at the 2nd, 7th and 28th day post surgery for: pain, oedema, haematoma, scar quality, suture dehiscence and infection. The numeric variables were presented in terms of mean and standard deviation. The normal distribution was checked by the Shapiro-Wilk test. Categorical variables were presented frequency and percentage. To compare the averages among the four independent groups, the Anova test was used and multiple comparisons were made by the Bonferroni correction. To verify categorical association in groups, the Pearson square test or Fisher's exact test were used. The software used was the SPSS18 and the level of significance below 0.05 was adopted for all variables analyzed. CONCLUSION: Continuous and separated skin suture using threads of poligalactine and catgut present similar results, as to the incidence of complications and quality of surgical scar. Surgical time is lower when the suture is continuous. Catgut thread presents lower cost, when compared with the use of poligactine. Medical conditions for surgical circumcision, educational level, skin color, tabacco use and use of medications did not influence the result of the surgery.